1988
DOI: 10.3109/00365548809117210
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Abscesses in Adults: An Analysis of 54 Consecutive Cases

Abstract: A retrospective analysis was performed of 54 consecutive adult patients with intracranial abscesses hospitalized between 1973 and 1985. Clinical signs and symptoms were varying and no single symptom was found in more than 48% of the patients. Also the laboratory findings were of limited diagnostic value. The etiology of the infections varied with the sources and could be identified in 42 of the patients. In patients with postoperative abscesses or infections after penetrating head injuries Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 15 publications
3
39
1
3
Order By: Relevance
“…본 연구에서도 수술 후 발생한 뇌농양의 배양 검사에서 S. aureus가 동정되었고, Gram-negative rod도 1례에서 확인되었다. 이성 뇌농양의 보고에서 가 장 흔한 세균은 Proteus spp인데 22) , 본 연구에서도 P. 뇌농양의 발생 위치와 동정된 세균은 감염원과 밀접한 관 련이 있다 [8][9][10]16,19,21) . 이성 감염에 의한 대부분의 뇌농양은 측 두엽과 두정엽 또는 소뇌에서 주로 발견되는데, 본 연구에서 는 이성 뇌농양의 2례가 측두엽에서 발생하였다.…”
Section: 대상 및 방법unclassified
“…본 연구에서도 수술 후 발생한 뇌농양의 배양 검사에서 S. aureus가 동정되었고, Gram-negative rod도 1례에서 확인되었다. 이성 뇌농양의 보고에서 가 장 흔한 세균은 Proteus spp인데 22) , 본 연구에서도 P. 뇌농양의 발생 위치와 동정된 세균은 감염원과 밀접한 관 련이 있다 [8][9][10]16,19,21) . 이성 감염에 의한 대부분의 뇌농양은 측 두엽과 두정엽 또는 소뇌에서 주로 발견되는데, 본 연구에서 는 이성 뇌농양의 2례가 측두엽에서 발생하였다.…”
Section: 대상 및 방법unclassified
“…Enterobacteriaceae and the Bacteroides group were isolated in mixed cultures, especially in cases secondary to otitis media [1]. Other studies have also shown that anaerobes were commonly encountered in cerebral pus [2][3][4][5].…”
Section: Accepted For Publication 22 August 1990mentioning
confidence: 99%
“…Bacteria gain access to the brain either by direct spread, accounting for 20 to 60% of cases, or through hematogenous seeding (2). While direct spread from contagious sites usually causes a single brain abscess, bacteremic spread typically causes multiple lesions (9). Primary infections that can directly spread to the cerebral cortex include subacute and chronic otitis media, mastoiditis, frontal or ethmoid sinusitis, and dental infections.…”
mentioning
confidence: 99%